Cardiovascular Involvement in Patients with Autosomal Dominant Polycystic Kidney Disease: A Review - Maria Pietrzak-Nowacka; Krzysztof Safranow; Edyta Płońska-Gościniak; Adam Nowacki; Piotr Późniak; Piotr Gutowski; Kazimierz Ciechanowski (Karger Publishers, 2023)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease with a prevalence of 1:400 to 1:1,000 in Caucasians. It is caused by mutations in the PKD1 gene located on chromosome 16p13.3 (in about 85% cases) as well as in the PKD2 gene on chromosome 4q13-23. In the Polish population, the disease is associated with PKD1 mutations in 84% of the ADPKD-affected families. PKD1 and PKD2 genes encode the proteins polycystin-1 (PC1) and polycystin-2 (PC2), respectively. The presence of kidney cysts is a characteristic feature in the ADPKD patients. But in the ADPKD patients, cardiovascular abnormalities, such as hypertension (HT) with higher systolic blood pressure (SBP) and diastolic blood pressure (DBP) values, higher left ventricular mass (LVM), intracranial (ICAN) and extracranial aneurysms, and cardiac valve defects, are significantly more common than in the general population. Summary: According to the literature data, both higher LVM and vascular dysfunction already occur in children and young adults with normal renal function and without HT. Moreover, biventricular diastolic dysfunction, endothelial dysfunction, increased carotid intima-media thickness, and impaired coronary flow velocity reserve are present even in young patients with ADPKD who have normal HT and well-preserved renal function. In patients with ADPKD, hypertension has some specific features; in the youngest age group of children, the prevalence of hypertension is greater if their parents suffer from hypertension; in normotensive young ADPKD-diagnosed individuals, ambulant SBP and DBP values were significantly higher than in age- and gender-matched controls; hypertension appears at least 10 years earlier than spontaneous HT in general population. In adults, HT is often diagnosed before any substantial reduction in the GFR, and a lower nocturnal dip in BP in comparison to hypertensives in the general population. PKD1 and PKD2 gene products (PC1 and PC2 proteins) have been shown to assemble at the plasma membrane and to regulate calcium (Ca2+) entry. A defect in Ca2+ binding mediated by mutations in polycystin proteins is a hypothetical factor contributing to left ventricular mass increase. Altered intracellular Ca2+ handling contributes importantly to impaired contractility associated with heart failure. Impairment of intracellular Ca2+ homeostasis and mitochondrial function has been implicated in the development of LVH. Key Messages: It can be assumed that the cause of LVH in ADPKD patients is the natural course of this disease with developing HT and deteriorating kidney function, which may be influenced by the presence of PKD1- and PKD2-mutated gene products: PC1 and PC2 proteins.